Most favoured nation (MFN) - a post Lomé alternative for the Caribbean (The Council LondonGB, 1998)
Concludes that for the Caribbean, the priority must be to identify a trade strategy that ensures that complimentary arrangements are in place to cover the complex matrix of relationships with both the Americas and the European Union after 2005. Suggests that by negotiating jointly with the EU for an MFN political coalition this can be achieved.
DC